Hubungan antara Konsep Diri dengan Prestasi Belajar Siswa SMA Dharma Putra Tangerang - Liauwrencia, Prisca Febrian; Putra, Denny (Noetic Psychology, 2014)
ÃÂ AbstrakStudents academic achievement in school influenced by many factors. They were internal and external factors and consist of many different factors. Literature findings showed different result among the factors. This research aimed to identify the relation between self concept and student academic achievement. Using purposive sampling technique, 32 highschool student were chosen as subject.ÃÂ ÃÂ ÃÂ Self concept measured by self concpet scale and academic achievent measured using academic report. Using parson product moment, these two variable were measured to analyze the relationship between them.ÃÂ The result showed that they were significant corelation between self concept and student academic achievement in highschool student (r = 0,381; p < 0,05). Kata kunci: academic achievement, self concept, highschool student